Oxygenation Impairment during Anesthesia: Influence of Age and Body Weight. (July 2019) - Hedenstierna, Göran; Tokics, Leif; Scaramuzzo, Gaetano; Rothen, Hans U.; Edmark, Lennart; Öhrvik, John
Editor's Perspective: What We Already Know about This Topic: During anesthesia oxygenation is impaired, especially in the elderly or obese, but the mechanisms are uncertain. What This Article Tells Us That Is New: Pooled data were examined from 80 patients studied with multiple inert gas elimination technique and computed tomography. Oxygenation was impaired by anesthesia, more so with greater age or body mass index. The key contributors were low ventilation/perfusion ratio (likely airway closure) in the elderly and shunt (atelectasis) in the obese. Background: Anesthesia is increasingly common in elderly and overweight patients and prompted the current study to explore mechanisms of age- and weight-dependent worsening of arterial oxygen tension (PaO2 ). Methods: This is a primary analysis of pooled data in patients with (1) American Society of Anesthesiologists (ASA) classification of 1; (2) normal forced vital capacity; (3) preoxygenation with an inspired oxygen fraction (FIO2 ) more than 0.8 and ventilated with FIO2 0.3 to 0.4; (4) measurements done during anesthesia before surgery. Eighty patients (21 women and 59 men, aged 19 to 69 yr, body mass index up to 30 kg/m 2 ) were studied with multiple inert gas elimination technique to assess shunt and perfusion of poorly ventilated regions (low ventilation/perfusion ratio [ ]) and computed tomography to assess atelectasis. Results: PaO2 /FIO2 was lower during anesthesia than awake (368; 291 to 470 [median; quartiles] vs . 441; 397 to 462 mm Hg; P = 0.003) and fell with increasing age and body mass index. Log shunt was best related to a quadratic function of age with largest shunt at 45 yr ( r 2 =0.17, P = 0.001). Log shunt was linearly related to body mass index ( r 2 = 0.15, P < 0.001). A multiple regression analysis including age, age 2, and body mass index strengthened the association further ( r 2 = 0.27). Shunt was highly associated to atelectasis ( r 2 = 0.58, P < 0.001). Log low showed a linear relation to age ( r 2 = 0.14, P = 0.001). Conclusions: PaO2 /FIO2 ratio was impaired during anesthesia, and the impairment increased with age and body mass index. Shunt was related to atelectasis and was a more important cause of oxygenation impairment in middle-aged patients, whereas low, likely caused by airway closure, was more important in elderly patients. Shunt but not low increased with increasing body mass index. Thus, increasing age and body mass index impaired gas exchange by different mechanisms during anesthesia. Abstract : Pooled data were examined from 80 patients studied with multiple inert gas elimination technique and computed tomography. Oxygenation was impaired by anesthesia, more so with greater age or body mass index. The key contributors were low ventilation/perfusion ratio (likely airway closure) in the elderly and shunt (atelectasis) in the obese.Supplemental Digital Content is available in the text.